Small means immoral? The impact of spatial size metaphor on moral judgment - Weirui Xiong; Jiaxin Wang; Jiayi Li (PLoS ONE, 2025)
This study aims to explore the unconscious relationship between moral concepts and the spatial dimension of size, as well as to examine whether the unknown size of a room influences participants’ moral cognitive judgments within the framework of embodied cognition. Study 1 and Study 2 investigate participants’ unconscious biases. Specifically, participants exhibited faster response times when judging moral concepts presented in large fonts and sizes and immoral concepts presented in small fonts and sizes, compared to when moral concepts were presented in small fonts and sizes and immoral concepts in large fonts and sizes. Study 3 employed a moral dilemma task, revealing that participants placed in a large room evaluated characters in a story more morally under the embodiment effect than those in a small room. Collectively, these three studies demonstrate that the unconscious psychological relationship between moral concepts and the spatial dimension of size influences individuals’ abstract moral judgments under embodied cognition.